Coastal Erosion Pattern and Rehabilitation of Climate Displaced Communities of 3 Coastal Islands in and Around the South-Eastern Coast of Bangladesh - Barua, Prabal; Rahman, Syed Hafizur; Mitra, Abhijit (Global Journal of Earth Science and Engineering, 2024)
Climate-induced displacement has evolved into a major global issue in recent years. Bangladesh experiences many forms of migration and human movement, which directly and indirectly impact national policies. In this book chapter, the authors explored the trend of coastal erosion and displacement of the communities of 3 coastal islands of the South-Eastern Coast of Bangladesh. Assessing the spatial dynamics of the coastal system requires looking back at the past development and temporal morpho-dynamics of shoreline position and shape. The current study set out to assess the potency of various statistical methods for forecasting shoreline changes and their dynamic nature. In this case, the vulnerability to coastal erosion was quantified using GIS and Remote Sensing. The authors examined how much the land area of Sandwip and Kutubdia islands has shrunk over the last 40 years (1957 to 2018), at rates of 0.822 and 0.242 times respectively. The neighbouring island, Maheskhali, is likewise experiencing coastline erosion, however satellite images show that the island's land area is growing 1.174 times every year. This is taking place as a result of new char land being formed at various points on the Maheskhali island, which has also eroded into the sea at various points. Even when the wind's direction changed and occurred at almost the same maximum values, the erosion scenario at Maheskhali, Sandwip, and Kutubdia remained unchanged. As a result, it may be concluded that Bangladesh's coastal erosion is relatively unaffected by wind speeds, despite fluctuations in wind direction. The authors explored that the rehabilitation of climate-displaced people is very limited compared to the large numbers of people displaced from the coastal islands. Besides, after the displacement, people lose their harmony, identity, and livelihood opportunities after migrating to? New places that are far from the origin. The authors found that if the community-based relocation program is introduced in the living places in the same areas for displaced people around the community living places, that will be most effective.